Management of Chronic Myelopathy Symptoms and Activities of Daily Living - Ganguly, Karunesh; Abrams, Gary M. (Seminars in Neurology, 2012)
Many disorders can injure the spinal cord resulting in long-term chronic myelopathy. Spinal cord dysfunction influences the homeostasis of multiple organ systems ranging from the heart or lung to the integument, thus presenting a wide variety of challenges for medical management. Although most of our knowledge about the consequences of myelopathies derives from the study of traumatic spinal cord injuries, similar complications occur in myelopathies of all etiologies. The authors survey some of the important clinical issues that the general neurologist needs to consider in caring for patients with chronic spinal cord disease.
Keywords: myelopathy; spinal cord injury; spasticity; pain